2019
DOI: 10.1055/a-0975-9595
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utilization of Pharmacogenetics in Psychiatry – Perspectives of Pharmacists, Genetic Counselors, Implementation Science, Clinicians, and Industry

Abstract: Introduction The use of pharmacogenomic (PGx) testing to guide decisions and improve patient outcomes has increased in recent years. PGx testing represents a decision support tool that may inform dosing, increase the likelihood of treatment response, and identify patients at risk for medication side effects. Methods This is a narrative review of utilization of PGx testing in psychiatry from stakeholders including, pharmacists, genetic counselors, implementation scientists, industry, and clinicians. Results Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 101 publications
1
19
0
Order By: Relevance
“…Our recommendation to advocate for preemptive genotyping for clinically actionable gene-drug pairs is also consistent with our previous analyses of the same data set (published elsewhere [20]) where we reported that genotyped patients responded earlier and better to antidepressant drugs and therefore had a shorter duration of stay in the hospital and lower rehospitalization rates [3,4,20].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Our recommendation to advocate for preemptive genotyping for clinically actionable gene-drug pairs is also consistent with our previous analyses of the same data set (published elsewhere [20]) where we reported that genotyped patients responded earlier and better to antidepressant drugs and therefore had a shorter duration of stay in the hospital and lower rehospitalization rates [3,4,20].…”
Section: Resultssupporting
confidence: 89%
“…A panel as proposed by Bousman et al should be the standard screening panel in psychiatric patients before starting a drug therapy [2]. By knowing the CYP genotype of the patient early on before drug therapy is started, chronicity of the disease and hospitalization, as well as adverse drug events, might be prevented, as suggested in the IMPACT study [26] and through meta-analyses [2,4]. Genotyping should be introduced into daily practice in psychiatric patients in the ambulatory setting to avoid admissions to a psychiatric hospital or increased healthcare utilization [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the genetic architecture of CYP26 is highly variable among individuals and has more than 100 known allelic variants [9]. These variations are important because they help explain inter-individual differences in hydroxylation capacities and are an important consideration when administering psychiatric medications [10]. The discovery of the cytochrome family of genes permitted widespread population studies to be conducted and importantly helped to understand some of the interethnic differences to drug reactions [11].…”
Section: Introduction To the History Of Pharmacogenetics Pre-twentietmentioning
confidence: 99%
“…The second article by Brown et al [2] notes that at the time of writing in 2019, there were 39 psychiatric drugs with pharmacogenomic language listed in their product labelling. Strikingly, 36 contain information on CYP2C19 and CYP2D6 metabolizer status, making both genes the primary targets in any implementation strategy for pharmacogenetic testing.…”
mentioning
confidence: 99%